Space diversity path loss in a modern factory at frequency of 2.4 GHz - Supachai Phaiboon (2018)
This paper presents radio wave propagation characteristics of a modern factory at a frequency of 2.4 GHz. Fading deeps from space diversity at transmitting and receiving antennas are proposed with measured data. These models provide both large scale fading and boundary limitation in which almost measured data is contained. There are five path loss categories, namely LOS, NLOS same area, NLOS different area, LOS+NLOS same area and LOS+NLOS all areas. These categories provide different path loss characteristics in each environment. Comparisons between conventional models and purposed models are discussed and show that the purposed models provide prediction with in boundaries for all categories, especially for LOS model and the wall attenuation factor (WAF) model. It is also found that machine arrangements do not affect significantly the path loss characteristics.